Commodification of Religion and Capitalism in Popular Culture: Religious Pop Music Industry in The Month of Ramadhan - Mafakhir, Muhammad Tajul; Zulaihah, Sitti (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
Today’s widespread cultural phenomenon has primarily the characteristic "commodity" of being dominated by exchange rates rather than utility values. Music as part of popular culture indeed becomes part of society’s commodity, where the cultural desires of society now more dominate the music industry. As for Indonesia is now born in pop religion music that starts in a community-centred culture, where people want to listen to religious music as a form of expression about themselves, especially in the month of Ramadan. For some people listening to Islamic songs or music can influence their emotions to become better acquainted with the Islamic religion. It is mainly made up of Ramadan, and many societies use religious music as a religious edification during Ramadan. From such a consumptive culture was born the komoged religion and capitalism in the religious pop music industry in Ramadan. The perpetrators of the music industry turned the moment Ramadan as momentum to capitalize and use Islamic religious symbols into the Muslim industry. The avalanche of Islamic music by Ramadan must be part of the capitalist strategy for making a profit by flexing the symbols found in the Islamic faith.